Preparation method of polymer solid electrolyte and negative-electrode-free solid sodium battery
By using polymer solid electrolyte and negative electrode-free solid sodium battery design in sodium ion batteries, the problems of low energy density and safety hazards of traditional sodium ion batteries are solved, and high energy density and excellent safety are achieved.
Patent Information
- Application Number
- CN202510075424.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-25
AI Technical Summary
Traditional sodium ion batteries have low energy density and pose safety risks, and the manufacturing difficulty and cost of ultra-thin metal sodium foils are difficult and costly.
Using polymer solid electrolytes and existing sodium ion battery positive electrode materials and metal current collectors, we build a negative electrode solid sodium battery, avoiding the use of highly active, water-oxygen-sensitive sodium foils and flammable liquid electrolytes.
It significantly improves the energy density of sodium ion batteries, reduces the difficulty and cost of manufacturing processes, and improves the safety performance and cycle life of the batteries.
Smart Images

Figure CN119890467A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of new energy technology and relates to a preparation method of a polymer solid electrolyte and a negative electrode-free solid sodium battery. Background Art
[0002] Compared with sodium-ion batteries, the energy density of sodium-ion batteries is inherently insufficient and it is difficult to meet the needs of high-energy consumption applications. In traditional sodium-ion batteries, carbon-based negative electrodes such as hard carbon account for more than 25% of the battery weight and more than 40% of the battery thickness, which is a key factor restricting the energy density of sodium-ion batteries. At the same time, traditional sodium-ion batteries use highly flammable and leaky organic electrolytes, which pose serious safety hazards. Using metallic sodium instead of carbon negative electrodes can significantly improve the energy density of batteries. However, ultra-thin metallic sodium foil has not yet been commercially manufactured. Ultra-thin metallic sodium foil with strong adhesion, fragility, and water-oxygen sensitivity also greatly increases the difficulty and cost of the battery manufacturing process.
[0003] By removing the carbon negative electrode material from the battery and constructing an ultra-thin metallic sodium negative electrode in situ through the release of sodium from the positive electrode, the negative electrode-free battery system is expected to greatly improve the energy density of sodium-ion batteries while reducing the difficulty and cost of battery manufacturing processes. The electrolyte is the core component of the negative electrode-free sodium battery, but the existing liquid electrolyte is flammable, easy to leak, and prone to side reactions on the positive and negative electrode sides, resulting in serious irreversible sodium loss, which greatly restricts the cycle life and safety of the negative electrode-free sodium battery. Summary of the invention
[0004] In view of the problems existing in the prior art, the present invention provides a method for preparing a polymer solid electrolyte and a solid sodium battery without a negative electrode. The present invention uses a Lewis acid initiator to initiate a cross-linking polymerization reaction of a cyclic ether to obtain a high ion conductivity polymer solid electrolyte at room temperature. The polymer solid electrolyte is used together with an existing sodium ion battery positive electrode material and a metal current collector to create a solid sodium battery without a negative electrode. The present invention can avoid using highly active, water-oxygen-sensitive sodium foil as a negative electrode, avoid the use of flammable liquid electrolytes, and solve the problems of low energy density and safety risks of traditional sodium ion batteries.
[0005] In order to achieve the above technical objectives, the technical solution adopted by the present invention is as follows:
[0006] A method for preparing a polymer solid electrolyte and a negative electrode-free solid sodium battery, the preparation method comprising the following steps:
[0007] In the first step, the sodium salt is dissolved in an organic solvent and a polymer monomer is added, followed by thorough stirring to obtain a solid electrolyte precursor solution.
[0008] In the second step, a polymerization initiator is added to the solid electrolyte precursor solution at room temperature to initiate a cross-linking polymerization reaction, and the solution is allowed to stand at room temperature for a certain period of time to obtain a polymer solid electrolyte.
[0009] The third step is to prepare the positive electrode of the sodium ion battery.
[0010] The fourth step is to add the polymer solid electrolyte between the positive electrode of the sodium ion battery and the metal current collector to prepare a negative electrode-free solid-state sodium battery.
[0011] Furthermore, in the first step: the organic solvent is ethylene glycol dimethyl ether; the sodium salt is at least one of sodium bis(trifluoromethanesulfonyl)imide, sodium nitrate, and sodium hexafluorophosphate. The polymer monomer is a cyclic ether, including at least one of 1,3,5-trioxane and 1,3-dioxolane. In the solid electrolyte precursor solution:
[0012] When the sodium salt is sodium bis(trifluoromethanesulfonyl)imide, the concentration of sodium bis(trifluoromethanesulfonyl)imide is 100-400 mg / mL. -1 ; When the sodium salt is sodium nitrate, the concentration of sodium nitrate is 10-50 mg mL -1 ; When the sodium salt is sodium hexafluorophosphate, the concentration of sodium hexafluorophosphate is 50-300 mg mL -1 .
[0013] When the polymer monomer is 1,3,5-trioxane, the mass content of 1,3,5-trioxane is 10-50%; when the polymer monomer is 1,3-dioxolane, the mass content of 1,3-dioxolane is 10-50%.
[0014] Furthermore, in the first step: the stirring speed is 400-600 rpm, the stirring time is 1-4 hours, and the stirring temperature is room temperature.
[0015] Furthermore, in the second step, the polymerization initiator is Al(OTf) 3 , concentration is 1-2 mg mL -1 ; The standing time is 2 to 8 hours.
[0016] Furthermore, in the third step, the positive electrode of the sodium ion battery is prepared by using a positive electrode material of the sodium ion battery, a conductive agent and a binder. Specifically, the positive electrode material of the sodium ion battery, the conductive agent and the binder are uniformly mixed in a mass ratio of 90:5:5, N-methylpyrrolidone is added as a solvent and a dispersant, and the resulting slurry is uniformly coated on a carbon-coated aluminum foil as a positive electrode of the sodium ion battery. The metal current collector is one of aluminum, copper, and stainless steel foil / mesh coated with a carbon layer on the surface.
[0017] Furthermore, the positive electrode material of the sodium ion battery is at least one of sodium nickel iron manganese oxide, sodium vanadium phosphate, sodium iron phosphate, and sodium iron phosphate pyrophosphate, and the positive electrode material loading of the positive electrode material of the sodium ion battery on the aluminum foil is 2 to 30 mg cm -2 ; The conductive agent is at least one of carbon black, carbon nanotubes, and graphene; the binder is polyvinylidene fluoride;
[0018] Furthermore, in the fourth step, after adding the solid electrolyte precursor solution between the positive electrode of the sodium ion battery and the metal current collector, a polymerization initiator is added according to the second step to encapsulate the battery.
[0019] The beneficial effects of the present invention are:
[0020] (1) The present invention adopts a polymer solid electrolyte to replace the flammable and leaky liquid electrolyte, thereby solving the problem of leakage of organic flammable electrolyte during battery use and improving the safety performance of the battery.
[0021] (2) Since no negative electrode material is used, the energy density of the new negative electrode-free solid-state sodium battery constructed by the present invention is >350Whkg -1 , which is much higher than traditional liquid sodium-ion batteries and has excellent safety under mechanical puncture conditions.
[0022] (3) The polymer solid electrolyte prepared in the present invention can achieve reversible sodium deposition-stripping, avoid irreversible loss of sodium, and extend the cycle life of the negative electrode-free sodium battery to 400 times.
[0023] (4) The present invention has a simple process for preparing anode-free solid-state sodium batteries, low cost, and can be directly applied to the existing production process of lithium / sodium ion batteries, and is suitable for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 is the infrared spectrum of the polymer solid electrolyte prepared in Example 1 of the present invention;
[0025] Figure 2 is the Raman spectrum of the polymer solid electrolyte prepared in Example 1 of the present invention;
[0026] Figure 3 is the cycle life of the negative electrode-free solid-state sodium battery prepared in Example 1 of the present invention;
[0027] Figure 4 : is the charge and discharge curve of the negative electrode-free solid-state sodium battery prepared in Example 1 of the present invention;
[0028] Figure 5 The safety of the negative electrode-free solid-state sodium battery prepared in Example 1 of the present invention under mechanical puncture. DETAILED DESCRIPTION
[0029] In view of the many defects of the prior art, the inventor of this case has proposed the technical solution of the present invention after long-term research and extensive practice. The technical solution, its implementation process and principle, etc. will be further explained as follows. However, it should be understood that within the scope of the present invention, the above-mentioned technical features of the present invention and the technical features specifically described in the following (embodiments) can be combined with each other to form a new or preferred technical solution.
[0030] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.
[0031] Example 1
[0032] 1) Sodium hexafluorophosphate was added to ethylene glycol dimethyl ether, and 1,3,5-trioxane monomer was added, and the mixture was stirred thoroughly to obtain a solid electrolyte precursor solution. The concentration of sodium hexafluorophosphate was 170 mg mL -1 ; The content of 1,3,5-trioxane is 30%; the stirring speed is 500 rpm, and the stirring time is 2 h.
[0033] 2) Adding a polymerization initiator to the solid electrolyte precursor solution prepared in step 1) and leaving it to stand at room temperature to obtain a polymer solid electrolyte. The polymerization initiator is Al(OTf) 3 , concentration 1mg mL -1 ; The standing time is 6h.
[0034] 3) Sodium vanadium phosphate positive electrode material, carbon black conductive agent and polyvinylidene fluoride binder were uniformly mixed in a mass ratio of 90:5:5, N-methylpyrrolidone was added as a solvent and dispersant, and the resulting slurry was uniformly coated on carbon-coated aluminum foil as a positive electrode. The positive electrode material loading was 10 mg cm -2 ; The conductive agent is polyvinylidene fluoride.
[0035] 4) Preparation of anode-free solid-state sodium batteries;
[0036] The solid electrolyte precursor solution obtained in step 1) is added between the positive electrode of the sodium ion battery obtained in step 3) and the metal current collector, and a polymerization initiator is added according to step 2) to encapsulate the battery. The metal current collector is an aluminum foil coated with a carbon layer.
[0037] The mass specific energy of the anode-free solid-state sodium battery prepared in this embodiment is greater than 350Wh kg -1 , cycle life of 400 times, and no smoke or fire under mechanical puncture conditions, with excellent safety.
[0038] Example 2
[0039] 1) Sodium hexafluorophosphate was added to ethylene glycol dimethyl ether, and 1,3-dioxolane monomer was added, and the mixture was stirred thoroughly to obtain a solid electrolyte precursor solution. The concentration of sodium hexafluorophosphate was 100 mg mL -1 ; The content of 1,3-dioxolane is 20%; The stirring speed is 400 rpm and the stirring time is 4 hours.
[0040] 2) Adding a polymerization initiator to the solid electrolyte precursor solution prepared in step 1) and leaving it to stand at room temperature to obtain a polymer solid electrolyte. The polymerization initiator is Al(OTf) 3 , concentration of 2 mg mL -1 ; The standing time is 6h.
[0041] 3) Sodium vanadium phosphate positive electrode material, carbon black conductive agent and polyvinylidene fluoride binder were uniformly mixed in a mass ratio of 90:5:5, N-methylpyrrolidone was added as a solvent and dispersant, and the resulting slurry was uniformly coated on carbon-coated aluminum foil as a positive electrode. The positive electrode material loading was 15 mg cm -2 ; The conductive agent is polyvinylidene fluoride.
[0042] 4) Preparation of anode-free solid-state sodium batteries;
[0043] The solid electrolyte precursor solution obtained in step 1) is added between the positive electrode of the sodium ion battery obtained in step 3) and the metal current collector, and a polymerization initiator is added according to step 2) to encapsulate the battery. The metal current collector is an aluminum foil coated with a carbon layer.
[0044] Example 3
[0045] 1) Add sodium bis(trifluoromethanesulfonyl imide) to ethylene glycol dimethyl ether, add 1,3,5-trioxane monomer, and stir thoroughly to obtain a solid electrolyte precursor solution. The concentration of sodium bis(trifluoromethanesulfonyl imide is 200 mg mL -1 ; The content of 1,3,5-trioxane is 50%; the stirring speed is 600 rpm, and the stirring time is 1 h.
[0046] 2) Adding a polymerization initiator to the solid electrolyte precursor solution prepared in step 1) and leaving it to stand at room temperature to obtain a polymer solid electrolyte. The polymerization initiator is Al(OTf) 3 , concentration of 2 mg mL -1 ; The standing time is 2h.
[0047] 3) Sodium vanadium phosphate positive electrode material, carbon black conductive agent and polyvinylidene fluoride binder were uniformly mixed in a mass ratio of 90:5:5, N-methylpyrrolidone was added as a solvent and dispersant, and the resulting slurry was uniformly coated on carbon-coated aluminum foil as a positive electrode. The positive electrode material loading was 15 mg cm-2 ; The conductive agent is polyvinylidene fluoride.
[0048] 4) Preparation of anode-free solid-state sodium batteries;
[0049] The solid electrolyte precursor solution obtained in step 1) is added between the positive electrode of the sodium ion battery obtained in step 3) and the metal current collector, and a polymerization initiator is added according to step 2) to encapsulate the battery. The metal current collector is a copper foil coated with a carbon layer.
[0050] Example 4
[0051] 1) Add sodium bis(trifluoromethanesulfonyl imide) to ethylene glycol dimethyl ether, add 1,3-dioxolane monomer, and stir thoroughly to obtain a solid electrolyte precursor solution. The concentration of sodium bis(trifluoromethanesulfonyl imide is 130 mg mL -1 ; The content of 1,3-dioxolane is 50%; The stirring speed is 500 rpm and the stirring time is 2 h.
[0052] 2) Adding a polymerization initiator to the solid electrolyte precursor solution prepared in step 1) and leaving it to stand at room temperature to obtain a polymer solid electrolyte. The polymerization initiator is Al(OTf) 3 , concentration of 2 mg mL -1 ; The standing time is 5h.
[0053] 3) Sodium vanadium phosphate positive electrode material, carbon black conductive agent and polyvinylidene fluoride binder were uniformly mixed in a mass ratio of 90:5:5, N-methylpyrrolidone was added as a solvent and dispersant, and the resulting slurry was uniformly coated on carbon-coated aluminum foil as a positive electrode. The positive electrode material loading was 20 mg cm -2 ; The conductive agent is polyvinylidene fluoride.
[0054] 4) Preparation of anode-free solid-state sodium batteries;
[0055] The solid electrolyte precursor solution obtained in step 1) is added between the positive electrode of the sodium ion battery obtained in step 3) and the metal current collector, and a polymerization initiator is added according to step 2) to encapsulate the battery. The metal current collector is a copper foil coated with a carbon layer.
[0056] The above-described embodiments merely express the implementation methods of the present invention, but they should not be understood as limiting the scope of the present invention. It should be pointed out that for those skilled in the art, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.
Claims
1. A method for preparing a polymer solid electrolyte and a negative electrode-free solid sodium battery, characterized in that: The preparation method comprises the following steps: In the first step, sodium salt is dissolved in an organic solvent and a polymer monomer is added, and the mixture is stirred thoroughly to obtain a solid electrolyte precursor solution; The second step is to add a polymerization initiator to the solid electrolyte precursor solution at room temperature to initiate a cross-linking polymerization reaction, and then stand at room temperature for a certain period of time to obtain a polymer solid electrolyte; The third step is to prepare the positive electrode of the sodium ion battery; The fourth step is to add the polymer solid electrolyte between the positive electrode of the sodium ion battery and the metal current collector to prepare a negative electrode-free solid-state sodium battery.
2. The method for preparing a polymer solid electrolyte and a cathode-free solid sodium battery according to claim 1, characterized in that: In the first step: the organic solvent is ethylene glycol dimethyl ether; the sodium salt is at least one of sodium bis(trifluoromethanesulfonyl imide), sodium nitrate, and sodium hexafluorophosphate; and the polymer monomer is a cyclic ether, including at least one of 1,3,5-trioxane and 1,3-dioxolane.
3. The method for preparing a polymer solid electrolyte and a cathode-free solid sodium battery according to claim 2, characterized in that: In the solid electrolyte precursor solution: When the sodium salt is sodium bis(trifluoromethanesulfonyl)imide, the concentration of sodium bis(trifluoromethanesulfonyl)imide is 100-400 mg mL -1 ; When the sodium salt is sodium nitrate, the concentration of sodium nitrate is 10-50 mg mL -1 ; When the sodium salt is sodium hexafluorophosphate, the concentration of sodium hexafluorophosphate is 50-300 mg mL -1 ; When the polymer monomer is 1,3,5-trioxane, the mass content of 1,3,5-trioxane is 10-50%; when the polymer monomer is 1,3-dioxolane, the mass content of 1,3-dioxolane is 10-50%.
4. The method for preparing a polymer solid electrolyte and a cathode-free solid sodium battery according to claim 1, characterized in that: In the first step: the stirring speed is 400-600 rpm, the stirring time is 1-4 hours, and the stirring temperature is room temperature.
5. The method for preparing a polymer solid electrolyte and a cathode-free solid sodium battery according to claim 1, characterized in that: In the second step, the polymerization initiator is Al(OTf)3, and the concentration is 1-2 mg mL -1 ; The standing time is 2 to 8 hours.
6. The method for preparing a polymer solid electrolyte and a cathode-free solid sodium battery according to claim 1, characterized in that: In the third step, the positive electrode of the sodium ion battery is prepared by using a positive electrode material of the sodium ion battery, a conductive agent and a binder.
7. The method for preparing a polymer solid electrolyte and a cathode-free solid sodium battery according to claim 6, characterized in that: The specific steps for preparing the positive electrode of the sodium ion battery are: uniformly mixing the positive electrode material of the sodium ion battery, the conductive agent and the binder in a mass ratio of 90:5:5, adding N-methylpyrrolidone as a solvent and dispersant, and uniformly coating the obtained slurry on the carbon-coated aluminum foil as the positive electrode of the sodium ion battery.
8. The method for preparing a polymer solid electrolyte and a cathode-free solid sodium battery according to claim 6, characterized in that: The positive electrode material of the sodium ion battery is at least one of sodium nickel iron manganese oxide, sodium vanadium phosphate, sodium iron phosphate, and sodium iron pyrophosphate; the conductive agent is at least one of carbon black, carbon nanotubes, and graphene; the binder is polyvinylidene fluoride; The positive electrode material loading of the sodium ion battery positive electrode material on the aluminum foil is 2 to 30 mg cm -2 .
9. The method for preparing a polymer solid electrolyte and a cathode-free solid sodium battery according to claim 1, characterized in that: In the fourth step, the metal current collector is one of aluminum, copper, and stainless steel foil / mesh with a carbon layer coated on the surface.
10. The method for preparing a polymer solid electrolyte and a cathode-free solid sodium battery according to claim 1, characterized in that: In the fourth step, after adding the solid electrolyte precursor solution between the positive electrode and the metal current collector of the sodium ion battery, a polymerization initiator is added according to the second step, and the battery is encapsulated.
Citation Information
Patent Citations
In-situ preparation and application of polymer solid electrolyte
CN114430064A
All-solid-state negative-electrode-free sodium ion battery and preparation method thereof
CN118943469A
Cited By
High-voltage-resistant polymer solid electrolyte, preparation method thereof and high-voltage all-solid-state sodium battery
CN120978190A